A fungal ribonuclease-like effector protein inhibits plant host ribosomal RNA degradation - Pennington,HG; Jones,R; Kwon,S; Bonciani,G; Thieron,H; Chandler,T; Luong,P; Morgan,S; Przydacz,M; Bozkurt,T; Bowden,S; Craze,M; et al. (2018)
ABSTRACT The biotrophic fungal pathogen Blumeria graminis causes the powdery mildew disease of cereals and grasses. Proteins with a predicted ribonuclease (RNase)-like fold (termed RALPHs) comprise the largest set of secreted effector candidates within the B. graminis f. sp. hordei genome. Their exceptional abundance suggests they play crucial functions during pathogenesis. We show that transgenic expression of RALPH CSEP0064/BEC1054 increases susceptibility to infection in monocotyledenous and dicotyledonous plants. CSEP0064/BEC1054 interacts in planta with five host proteins: two translation elongation factors (eEF1α and eEF1γ), two pathogenesis-related proteins (PR5 and PR10) and a glutathione-S-transferase. We present the first crystal structure of a RALPH, CSEP0064/BEC1054, demonstrating it has an RNase-like fold. The protein interacts with total RNA and weakly with DNA. Methyl jasmonate levels modulate susceptibility to aniline-induced host RNA fragmentation. In planta expression of CSEP0064/BEC1054 reduces the formation of this RNA fragment. We propose that CSEP0064/BEC1054 is a pseudoenzyme that binds to host ribosomes, thereby inhibiting the action of plant ribosome-inactivating proteins that would otherwise lead to host cell death, an unviable interaction and demise of the fungus.